Why don't more young men in the UK become fathers?. Issue 1 (February 1994) - Cartwright, A
Abstract : OBJECTIVE--This paper aims to show that, compared with young women, there is an apparent discrepancy in the reported sexual behaviour of young men and records of their fatherhood. DESIGN--The data come from four studies of the sexual behaviour of young people in various parts of Britain between 1960 and 1990 and from statistics published by the Office of Population Censuses and Surveys. MAIN RESULTS--More of the young men than the young women had been sexually active, and the men had had more sexual partners. Relatively few men under 20, however, are identified as fathers. In 1991 there were 52, 396 live births to women under 20 years, but only 12, 959 births were attributed to men under 20, and if all those to women under 20 for which the father was not identified are added to this, the total is still only 28, 208--54% of the number of births to women of that age. Seven possible reasons for the discrepancy are discussed. Data suggest that the two most probable explanations are that there are different patterns of intercourse among young men and women and that the data obtained in surveys are to some extent inaccurate or biased. CONCLUSIONS--Differing behaviours indicate a double standard for men and women. Imperfect information affects predictions about a potential heterosexual HIV epidemic.